PENGEMBANGAN ALAT PERMAINAN EDUKATIF ULAR TANGGA DALAM PEMBELAJARAN MATEMATIKA KELAS II SDN 9 NEGERIKATON - Yulita Dwi Lestari; Anisa Urrohmah; Joko Sutrisno AB (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT This research uses development research. This research is motivated by the unavailability of snakes and ladders educational game tools as learning media in mathematics. Snakes and ladders educational game tool media is good to use because it can make it easier for educators to carry out learning, students can also learn while playing so that the process of learning activities feels fun and not boring. Based on the research results, it was obtained that the material validation was 90.38% with the criteria of "very feasible". The media expert validation results were 100% with the "very feasible" criteria. The results of the educator's response were 91.17% included in the "very interesting" category. The results of student responses to product trials with a percentage of 96% fall into the "good" category and can already be said to be "interesting". The average learning outcomes of mathematics using the snake and ladder educational game tool with a score of 85 from 37 students who took part in the product trial, and obtained an effectiveness of 100%. All students have achieved the minimum score and everything is complete.